Towards Better Software Development Effort Estimation with Analogy-based Approach and Nature-based Algorithms - Sarpiri, Mona Najafi; Aghaei, Mohammadreza Soltan; Gandomani, Taghi Javdani (International Conference on Information Technology Research (Online), 2023)
Software effort estimation has always been among the main considerations of software practitioners and researchers. A project's proper cost estimation is crucial for the organization's conservation and competitiveness; thus, excessive overestimation or underestimation of software development cost is a key factor for the failure of software products or closing software projects without any special achievement. The cost considered for software system development mainly pertains to the human efforts whose amount is calculated using the time span and the number of individuals involved in a project. The research behind software effort estimation is generally focused on providing solutions for improving the estimation, resulting in different approaches for improving software effort improvement. One of the most prevalent approaches is analogy-based estimation. The literature review indicates the significant and positive results of this approach in software effort estimation; however, there are still serious research gaps. This article attempts to address the research gaps and novel trends ahead of software researchers in analogy-based effort estimation.